Market Development Strategy for Underdeveloped Village Economy Based on Sharia Core Business - Nabillah Shallihah Henu (Journal of Islamic Economic and Business Studies, 2024)
The development of traditional markets in underdeveloped villages with low incomes must be done. This is because many markets have not met the standards both physically and operationally. This research aims to develop traditional markets in underdeveloped villages to keep up with the times and be able to increase the economic income of rural communities. By developing strategies based on sharia business core, application in financial management, and assistance from the government. This research uses the library method with secondary materials. The information used consists of empirical data obtained from various sources such as books, journals, official research reports, scientific literature, scientific articles, and other sources that support the focus of this research. This data collection method involves the process of reading, understanding, and analyzing information from various reading sources related to the research topic. The application of market development strategies in villages based on sharia business cores and the application of development in financial management is expected to help develop markets in villages.